The structure of learner varieties - Hendriks, Henriëtte (Studies on language acquisition, 2005)
Biographical note: Henriëtte Hendriks is Assistant Director of Research at the Research Centre of English and Applied Linguistics, University of Cambridge, Great Britain.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Funktionalismus; Fremdsprachenlernen